The unique cognitive phenotype of ASD + ADHD co-occurrence: evidence for planning and attention deficits as a differentiating approach - Wang, Tiantian; Bai, Miaoshui; Zhang, Zunwei; Jia, Feiyong (Frontiers in Pediatrics, 2026)
PurposeThis study aimed to assess cognitive processing in children with autism spectrum disorder (ASD) without co-occurring attention-deficit/hyperactivity disorder (ADHD) (ASD-alone), children with ADHD without co-occurring ASD (ADHD-alone), and children with ASD with co-occurring ADHD (ASD + ADHD).MethodsChildren were divided into four groups: ASD-alone (n = 57), ADHD-alone (n = 89), ASD + ADHD (n = 56), and typical development (TD) (n = 58). The Das–Naglieri Cognitive Assessment System (D-N CAS) was applied to evaluate planning, attention, simultaneous, and successive cognitive processes.ResultsChildren with ASD-alone scored less on planning processing. Children with ADHD-alone scored lower on planning and attention processing. Children with ASD + ADHD scored lower on all four processes. Planning and attention exhibited satisfactory stratification precision in identifying ASD + ADHD among children with ASD, with area under the curve (AUC) values of 0.7426 and 0.8061, respectively. Successive processing had medium diagnostic value in diagnosing ASD + ADHD among children with ADHD, with an AUC of 0.618. Inattention symptoms were associated with planning and attention processing. Social affects and inattention symptoms were associated with the total D-N CAS score.ConclusionChildren with ASD-alone, ADHD-alone, and ASD + ADHD exhibited distinct cognitive profiles. The D-N CAS, particularly its planning and attention scales, provided an approach for differential diagnosis in clinical settings.